2016
DOI: 10.3390/cli4020029
|View full text |Cite
|
Sign up to set email alerts
|

Urban-Rural Temperature Differences in Lagos

Abstract: Abstract:In this study, the hourly air temperature differences between City hall (urban) and Okoafo (rural) in Lagos, Nigeria, were calculated using one year of meteorological observations, from June 2014 to May 2015. The two sites considered for this work were carefully selected to represent their climate zones. The city core, City hall, is within the Local Climate Zone (LCZ 2) (Compact midrise) while the rural location, Okoafo, falls within LCZ B (Scattered Trees) in the south-western part on the outskirt of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 26 publications
6
40
0
Order By: Relevance
“…The study found that maximum nocturnal LST magnitudes in Lagos can exceed 7°C during the dry season, and during the rainy season, wet soils in the rural environment supersede regional wind speed as the dominant control over LST magnitude. The study of Ojeh et al (2016) was in agreement with Balogun et al (2012), which found that nocturnal heat island was more frequent than the day-time heat island over Akure city, Nigeria. More recently, studies have employed remote sensing and GIS techniques to analyze and quantify the effect of Land-use/Land-cover (LULC) change on LST (Ishola.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…The study found that maximum nocturnal LST magnitudes in Lagos can exceed 7°C during the dry season, and during the rainy season, wet soils in the rural environment supersede regional wind speed as the dominant control over LST magnitude. The study of Ojeh et al (2016) was in agreement with Balogun et al (2012), which found that nocturnal heat island was more frequent than the day-time heat island over Akure city, Nigeria. More recently, studies have employed remote sensing and GIS techniques to analyze and quantify the effect of Land-use/Land-cover (LULC) change on LST (Ishola.…”
Section: Introductionsupporting
confidence: 84%
“…In view of the above, earlier studies have identified LST also known as surface urban heat island (SUHI) by assessing measured rural-urban temperature differences (Balogun et al, 2012;Ojeh et al, 2016) in some areas in Nigeria. For instance, Ojeh et al (2016) investigated urban temperature conditions based on the hourly air temperature difference between City hall (Urban area) and Okoafo (Rural area) in Lagos, Nigeria. The study found that maximum nocturnal LST magnitudes in Lagos can exceed 7°C during the dry season, and during the rainy season, wet soils in the rural environment supersede regional wind speed as the dominant control over LST magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Urbanization provides a positive development for the population, but it also has negative consequences [3,4] for the environment, such as the urban heat island (UHI), high population density, emission of greenhouse gasses (GHG), air pollution, and high demand for energy [5,6]. Changing the composition of the urban land structure and transforming the naturally vegetated land into the built-up area have been mainly caused by the formation of the UHIs [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this context, the authors focus Lagos City as a research field in this study. Lagos City is the landmark of the Federal Republic of Nigeria and the second most populous and fast-growing city in Africa [5,8]. Lagos was developed as a port city since the colonial period, and it was developed after the petroleum booming between 1970 and 1980 [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The released anthropogenic heat is trapped in a very shallow surface layer where the atmospheric stability impedes the vertical mixing. In the stably stratified atmosphere, even relatively modest heat fluxes can significantly raise temperatures as they warm only a limited amount of air (Esau et al 2012, Davy and Esau 2014, 2016. This mechanism gives an amplifying factor to the UHI in mid-sized arctic cities.…”
Section: Discussionmentioning
confidence: 99%